2007
DOI: 10.1093/intqhc/mzn025
|View full text |Cite
|
Sign up to set email alerts
|

Quality of informed consent for invasive procedures

Abstract: Most patients do not remember receiving explanations about risks or alternatives for procedures, and physicians resist attempts to improve informed consent. Tools should be developed to measure the quality of consent. Since patients significantly differ in their preferred mode of decision-making, the informed consent should be patient-specific.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
75
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 19 publications
0
75
0
1
Order By: Relevance
“…Recent studies indicate that the majority of surgical consent discussions fail to meet criteria for fully informed consent. 25,26 It may be that decision aids designed to convey risks and benefits of cardiac surgical intervention in frail patients, particularly with regard to increased rates of prolonged institutional care, hospital mortality, and reduced long-term survival, would afford a more fully informed, shared decisionmaking process. It is equally important that the providers of cardiac surgical care work to mitigate the risks faced by frail patients through modification of processes of care.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicate that the majority of surgical consent discussions fail to meet criteria for fully informed consent. 25,26 It may be that decision aids designed to convey risks and benefits of cardiac surgical intervention in frail patients, particularly with regard to increased rates of prolonged institutional care, hospital mortality, and reduced long-term survival, would afford a more fully informed, shared decisionmaking process. It is equally important that the providers of cardiac surgical care work to mitigate the risks faced by frail patients through modification of processes of care.…”
Section: Discussionmentioning
confidence: 99%
“…We wanted to have more robust comparison of the findings of our study with similar published literature from particularly the other developing countries in our neighborhoods, however we could not find any quality publications from these countries. In glaring contrast to this situation, the majority of studies published from the developed countries are more focused on patients' perspectives of the process of SIC, with a recent growing trend towards the use of multimedia in the process and their impact on the patient's understanding of the content of SIC (32)(33)(34)(35)(36)(37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…It is important how a physician formulates the information presented to the patient, as it has been shown that patients often do not recollect all information provided by a physician (8), and the physicians often estimate that patients do not understand the obtained information on the health condition and possibilities of treatment (19). Nevertheless, the majority of physicians respect patients' autonomy and their decisions and requires the consent of relatives when the patient is not capable of reaching a decision (27).…”
Section: Discussionmentioning
confidence: 99%